2017
DOI: 10.1049/el.2017.3096
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐inspired signal detection mechanism for tongue click waveform used in human echolocation

Abstract: Human echolocation is the ability of an individual (which is often a blind person) to use his/her signal such as sound from tongue clicks to perceive the surrounding. Basically this requires the person to listen and analyse to the return echo of the tongue clicks. The main characteristics of the tongue click signal waveform have been reported, however the fundamental principle on a person's ability to identify his/her own signal is still vague. The possible detection mechanism of the tongue click signal wavefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The benefit of GF processing are as follows: (i) its ability in resolving the rich contents of the signal in much detail [18], (ii) implementation in time‐domain to avoid the demanding complex spectral computation, which helps in miniature hardware design [19] compare to others auditory filter scheme. The needs of a specific number of channels used upon processing could be a drawback, but overall GF processing is still an ideal method in synthesising human echolocator click as reported in [12, 22]. Hereby, the scope of this paper is to focus on AF performance of synthesising the human echolocator click using an auditory filter which is limited to GF processing only.…”
Section: Bio‐inspired Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of GF processing are as follows: (i) its ability in resolving the rich contents of the signal in much detail [18], (ii) implementation in time‐domain to avoid the demanding complex spectral computation, which helps in miniature hardware design [19] compare to others auditory filter scheme. The needs of a specific number of channels used upon processing could be a drawback, but overall GF processing is still an ideal method in synthesising human echolocator click as reported in [12, 22]. Hereby, the scope of this paper is to focus on AF performance of synthesising the human echolocator click using an auditory filter which is limited to GF processing only.…”
Section: Bio‐inspired Processingmentioning
confidence: 99%
“…The following study demonstrated that an ideal autocorrelation function (ACF) is achieved by adopting gammatone filter (GF) processing and solved the limitation encounter by matched filter (MF) method for human echolocation waveform [12]. Therefore, this study used GF approaches to synthesise sound signal prior to relay it into ambiguity function (AF) processing for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, features of a true pair of transmission–echo signals are scattered within the same cluster. Improved detection of human mouth-clicks was achieved with a bio-inspired (BI) processing approached over the matched filter (MF) outcome [ 23 , 24 ]. The BI process utilized a gammatone filter (GF) process in order to synthesize the mouth-click that was used in the detection process.…”
Section: Introductionmentioning
confidence: 99%